An Ab Initio Metadynamics Study Reveals Multiple Mechanisms of Reactivity by a Primal Carbon Cluster Toward Hydrogen and Ammonia in Space - Dobromir A. Kalchevski; Stefan K. Kolev; Dimitar V. Trifonov; Ivan G. Grozev; Hristiyan A. Aleksandrov; Valentin N. Popov; Teodor I. Milenov (Nanomaterials, 2025)
We present a theoretical model of the hydrogenation and amination of a primal carbon cluster of the tangled polycyclic type. Hydrogen atoms were introduced via H2, while the nitrogen source was NH3. The initial chemical processes were modeled using Born–Oppenheimer Molecular Dynamics. Metadynamics was employed to accelerate the saturation. The reactions were characterized in terms of barriers, topology, and intricate changes in the electronic structure. All transition states were identified. Multiple mechanisms for each type of reaction were discovered. Occasional unbiased changes in the carbon skeleton, induced by the guided processes, were observed. The initial addition reactions had no barriers due to the instability and high reactivity of the carbon structure. The final product of barrierless hydrogen saturation was C25H26. This molecule included multiple isolated double bonds, a medium-sized conjugated π system, and no triple bonds. Ammonia additions resulted in quaternary ammonium groups and primary amino groups. In the subsequent amination, a barrier appeared in fewer steps than in repetitive hydrogenation. The final product of barrierless saturation with NH3 was C25H2(NH3)2NH2. Further amination was characterized by a forward free-energy barrier of an order of magnitude larger than the reverse reaction, and the product was found to be unstable.